2021
DOI: 10.3390/vetsci8020015
|View full text |Cite
|
Sign up to set email alerts
|

Trichuris spp. in Animals, with Specific Reference to Neo-Tropical Rodents

Abstract: Trichuriasis is the clinical disease of animals infected with the parasite of the genus Trichuris. This review attempts to present information on Trichuris spp. infestation in neo-tropical rodents that are utilized for meat consumption by humans. Neo-tropical rodents utilized for meat production can be divided into two categories: those that have been domesticated, which include the guinea pig (Cavia porcellus), and those that are on the verge of domestication, such as the capybara (Hydrochoerus hydrochaeris),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 95 publications
(164 reference statements)
1
11
0
Order By: Relevance
“…The prevalences of Trichuris species and their infection intensities in sheep were investigated in the northern Xinjiang region. Existing studies have confirmed that there are approximately 24 species of Trichuris which parasitise ruminants (11,26,27). In this epidemiological survey, 6 documented species and 1 undefined species of Trichuris were found in sheep in Xinjiang and characterised.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The prevalences of Trichuris species and their infection intensities in sheep were investigated in the northern Xinjiang region. Existing studies have confirmed that there are approximately 24 species of Trichuris which parasitise ruminants (11,26,27). In this epidemiological survey, 6 documented species and 1 undefined species of Trichuris were found in sheep in Xinjiang and characterised.…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, distinguishing Trichuris females corresponding to each species of male was difficult because of coinfection with several species. Therefore, females were not identified in this study, and the identification of Trichuris species was based on the key characteristics of the reproductive organs of adult males as is common practice (6,11,15,20). Studies have revealed that the features such as the body length, the whip length to body length proportion, the length of the spicule and its sheath, and the morphometric characteristics of the spines of the spicule sheath are of high discriminatory value in differentiating Trichuris species (6,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…present in its gastrointestinal tract but the species was not identified. Further to this, Jones [2] reviewed Trichuris spp. found in rodents.…”
Section: Introductionmentioning
confidence: 99%